MANFAAT BIDARA DALAM KEHIDUPAN MANUSIA - Afiya Nur Fadhillah, Mufida; Efendi, Efendi; Faizin (Wahana Islamika, 2025)
The mention of the bidara plant in the Qur'an implicitly shows its superiority and high status. The bidara plant is mentioned twice, in the letter Saba' verse 16 and the letter Al-Waqi'ah verse 29. In addition to the Qur'an, there are several hadiths of the Prophet SAW explaining the various benefits of this bidara plant. In this article, the author tries to explain the content contained in the bidara plant and its benefits in human life. By searching various literature sources through the Google Scholar application, many benefits of this bidara plant were found. Along with the development of science and technology, the bidara plant is widely used in human life such as in the fields of health, spirituality and beauty.